Definición de un procedimiento de análisis de modelos de relaciones cívico-militares (Revista del Instituto Español de Estudios Estratégicos, 2018)
Following Huntington’s construct in The Soldier and the State, healthycivil-military relations (CMR) strike a balance between two imperatives-functional and societal- which maximizes military effectivenesswithout harming the democratic nature of the state. Maintaining thestability of a CMR pattern demands constant monitoring, so as to beable to identify flaws that might break the balance.The paper proposes a model for analysis of CMR patterns that coversfour areas: Professional Autonomy, Military Participation in Policy-making,Relation of the Military with its Civil Society, and Military Nonpartisanship.It then tries to define the optimum point of balance ineach area to outline how an “ideal” CMR profile should look like. Thepaper, then, applies the model to two cases that are compared againstthe proposed one. At the end, the paper draws some general conclusionsand identifies issues left open for further research.